The Role of the Distance between Fine Non-Metallic Oxide Inclusions on the Fatigue Strength of Low-Carbon Steel - Tomasz Lipiński (Applied Sciences, 2023)
The fatigue strength of steel is an important parameter determining the use of the alloy. Conducting material durability tests depending on the working conditions of the material requires a lot of work. Therefore, the industry knows methods to estimate the fatigue life of steel on the basis of other parameters or measurements of other mechanical properties. One of such parameters is the fatigue strength coefficient, which allows one to link the fatigue strength with the hardness results of a specific steel grade. Alloys produced in industrial conditions contain impurities that can affect the properties of steel, including fatigue strength. Impurities in steel depend mainly on the technology of its production. One of the technologies that allows one to obtain high-purity steel is by subjecting it to secondary metallurgy treatment consisting of desulfurization and refining with argon. The fatigue strength of steel depends, among other things, on the morphology of impurities. In the work, the influence of the distance between small non-metallic inclusions with a diameter of less than 2 µm on the fatigue strength of steel, expressed by the fatigue resistance factor, was assessed. The research was carried out in industrial conditions on seven independent melts of low-carbon steel capable of forming a martensite microstructure. Several dozen fatigue strength tests were carried out for each of the casts. The volume fraction, size, and distribution of pollutants were examined. It was found that the main impurity is Al2O3, with a diameter of about 1.8 µm occurring at a distance of about 12 µm. The distance between small non-metallic inclusions affects the fatigue resistance factor, and small non-metallic inclusions with a diameter of less than 2 µm hinder the destruction of high-ductility steel. The paper presents an example of the structure of non-metallic inclusions for heat, the relative volume of inclusions, the average impurity diameter and impurity spacing for impurity dimensional ranges, the impurity spacing λ for the total volume of impurities, and the bending fatigue strength coefficient tested in steel after hardening and tempering at different tempering temperatures.